The Implementaion of Habituation Method of Early Age Students and the Characteristics in the Islamic Boarding School of Salafiyah - Muhlisin; Sholikhatun (MUWAZAH : jurnal kajian gender, 2020)
This research is based on facts about the increasing of Islamic boarding school for early age students. Does the existence of the increase can be an institution that can accommodate the development of the mental of children? As a golden age, early ages become a very strategic entrance to the continuing of children education in the stage of elementary school to the next stages. To determine the level of effectiveness, it certainly depends on many factors, among which is the method that is applied by the manager of the boarding school. This study aims to explore and analyze the implementation of the habituation method to the early age students in Islamic Boarding School of Salafiyah, Proto, Kedungwuni, Pekalongan Regency. To uncover the data comprehensively, the researchers applied a qualitative approach, referring to the standard of field research. The source of data is obtained from the caretaker, teachers, and the representative of early age students randomly, through interviews, observations, and documentation study. To examine the validity of data, the researchers use triangulation of source of data, observation and theories. The technique of analyzing data is conducted through reduction, display, and verification of data. The results of the research showed that the application of the habituation method in daily activities for early age students emphasize on amaliyah diniyah yaumiyah. The habituation of students prioritizes daily ethics, taking ablution, praying in congregation, reciting the Koran, daily prayers, and maintaining cleanliness. However, the habituation has not concerned the cognitive domain in a standardized manner as the cognitive instructions are handed over to schools where students study formally; the boarding school is paid more attention to the affective and psychomotor domains. Their habitual characteristics take place naturally without any obvious standards. As a boarding school of early age students of Salafiyah, the students are more directed at habituation to live in the family as is usual. While the caretaker and teachers have run optimally like their parents themselves.